Multilocus Sequence Typing Methods for the Emerging Campylobacter Species C. hyointestinalis, C. lanienae, C. sputorum, C. concisus, and C. curvus - Miller, William G.; Chapman, Mary H.; Yee, Emma; On, Stephen L.; McNulty, Desmond K.; Lastovica, Albert J.; Carroll, Anne M.; McNamara, Eleanor B.; Duffy, Geraldine; Mandrell, Robert E. (Frontiers in Cellular and Infection Microbiology, 2012)
Multilocus sequence typing (MLST) systems have been reported previously for multiple food- and food animal-associated Campylobacter species (e.g. C. jejuni, C. coli, C. lari and C. fetus) to both differentiate strains and identify clonal lineages. These MLST methods focused primarily on campylobacters of human clinical (e.g. C. jejuni) or veterinary (e.g. C. fetus) relevance. However, other, emerging, Campylobacter species have been isolated increasingly from environmental, food animal or human clinical samples. We describe herein MLST methods for five emerging Campylobacter species: C. hyointestinalis, C. lanienae, C. sputorum, C. concisus and C. curvus. The concisus/curvus method uses the loci aspA, atpA, glnA, gltA, glyA, ilvD and pgm, whereas the other methods use the seven loci defined for C. jejuni (i.e., aspA, atpA, glnA, gltA, glyA, pgm, and tkt). Multiple food animal and human clinical C. hyointestinalis (n=48), C. lanienae (n=34) and C. sputorum (n=24) isolates were typed, along with 86 human clinical C. concisus and C. curvus isolates. A large number of sequence types (STs) were identified using all four MLST methods. Similar to Campylobacter MLST methods described previously, these novel MLST methods identified mixed isolates containing two or more strains of the same species. Additionally, these methods speciated unequivocally isolates that had been typed ambiguously using other molecular-based speciation methods, such as 16S rDNA sequencing. Finally, the design of degenerate primer pairs for some methods permitted the typing of related species; for example, the C. hyointestinalis primer pairs could be used to type C. fetus strains. Therefore, these novel Campylobacter MLST methods will prove useful in speciating and differentiating strains of multiple, emerging Campylobacter species.